New record species- from the family Euphorbiaceae in Iraq - Al-Musawi, Ali; Majeed, Isra,a (Iraqi Journal of Science, 2023)
The present work included morphological, anatomical, and palynologicalcharacters for the new species Acaalypha australis L. specimens, which belong tothe family Euphorbiaceae. The species recorded in the study for the first time inIraq. The plants of this species are annual herbs with green, striated or sub –polygonal stem, and branched near bases, Leaves are simple spirally alternate andlanceolate in shape. Flowers are unisexual, arranged in the axial of distinct leafy andcordate bracts, female flower arranged at the bracts bases and each flower withtrileafed perianth and superior ovary with trilobed stylar stigma which has dense andcoiled stigmatic hairs. Male flowers are arranged as a mixed verticellateinflorescence and enclosed by tetraleafed perianth. Each perianth leaf is similar tothat of the female flowers. Each male flower has eight free stamens, each with twoseparated anther sac. Pollen are spherical and belong to the small size and they aretri-tetra-colporate with vague sculpturing. Anatomicaly, section of root and stemcharacterized the presence of secondary growth and vascular cambium, in additionto collenchyma and seclerenchyma as a supported tissue. Druses crystals are alsopresent in the epidermal and cortical cells. Vertical section of leaves arecharacterized by similarity of tissue layers of petiole and leaf midribe, and presenceof oil bodies within the mesophyll.